Optimization of machining parameters values during milling on carbon fiber reinforced plastic (CFRP) using RSM - Ramli, Siti Fatirah; Muhamad Khairussaleh, Nor Khairusshima; Mokhtar, Suhaily; Dahnel, Aishah Najiah; A. Raof, Natasha (Malaysian Tribology Society (Mytribos), 2022)
This paper presents the optimization of machining parameters, namely cutting speed, feed rate, and depth of cut during milling on CFRP. The tool life analysis was developed using Analysis of Variance (ANOVA) and guided by Box Behnken Design as the Design of Experiment for this research. The input variables are cutting speed from 50.24 m/min to 218.54 m/min, feed rate from 0.03 mm/tooth to 0.25 mm/tooth and depth of cut from 1.0 mm to 1.5 mm. Optimum machining parameters were obtained based on the value of longest tool life as well as the desirability value near to one. As for 0-degree fiber orientation, the optimum machining parameters needed are cutting speed 218.54 m/min, feed rate of 0.03 mm/tooth and 1.21 mm depth of cut. Meanwhile for 45-degree fiber orientation, 218.31 m/min cutting speed, 0.05 mm/tooth feed rate, and 1.0 mm of depth of cut were utilized. The optimum machining parameters for 90-degree fiber orientation is 214.44 m/min of cutting speed, 0.04 mm/tooth of feed rate, and depth of cut of 1.22 mm. It was found out from ANOVA Analysis that feed rate was the most significant factor that affected the tool life during milling on CFRP.